Transformation of Character Education in Madrasahs: Implementing Value-Based Islamic Education Management - Muhamad Siswanto (English Education Program Universitas Pendidikan Muhammadiyah Sorong, 2024)
Character education in madrasahs plays a crucial role in shaping the morals and personalities of students, grounded in the values of Islam as reflected in the Qur'an and Hadith. Despite the challenges posed by globalization and technological advancements that influence students' mindsets, character education in madrasahs must continue to emphasize moral and spiritual values. Value-based Islamic education management is an effective approach to managing character education, involving all stakeholders, from madrasah administrators and educators to parents. This research employs a qualitative method with a literature study. The findings of this study indicate that character education in madrasahs has a strong foundation in Islamic teachings that emphasize the development of noble character as an integral part of education. Despite facing challenges such as external cultural influences and value mismatches between school and family, character education in madrasahs can still thrive through collaboration between madrasahs, parents, and the community. Value-based Islamic education management plays a vital role in organizing education with Islamic principles that prioritize the development of students' spiritual and social values. The transformation of character education through an effective managerial approach, including visionary leadership, careful planning, and continuous evaluation, will create an environment conducive to the development of students' character. With proper management and cooperation from all parties, character education in madrasahs can produce students who are not only intelligent but also virtuous, ready to face life’s challenges with strong integrity.